The peasant the buffalo and the tiger : Vietnamese legends and tales / Hoa Mai, Hữu Ngọc - Hoa, Mai
Vietnamese legends and tales: The peasant, the buffalo and the tiger. legend of Tan Vien Moutain. The Toad and the Rain. The legend of the "Banh Day" and the "Banh Chung".